Task Complexity And Students’ Narrative Writing - Dahlan Dahlan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
This article is a theoretical review writing. It explores some studies on the effects of task complexity on written narrative production under different task complexity conditions by EFL learners at different proficiency levels. Task complexity was manipulated along Robinson’s (2001b) proposed task complexity dimension of Here-and-Now (simple) vs. There-and-Then (complex) in. Accordingly, three specific measures of the written narratives were targeted, i.e. complexity, accuracy and fluency (CAF). The results of some experts’ research indicated that with respect to complexity and accuracy, the effects of both task complexity and language proficiency were found significant. More complexity and accuracy were found in the complex task with high-proficiency learners. However, no significant effect of task complexity and language proficiency on fluency was found. The pedagogical implications are discussed with reference to the influence of task complexity and language proficiency on text quality.